2021
DOI: 10.1021/acs.jafc.0c07237
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoactivated Toxicity of 2-Thiophenylfuranocoumarin Induce Midgut Damage and Apoptosis in Aedes aegypti Larvae

Abstract: Furanocoumarins are photoactive compounds derived from secondary plant metabolites. They possess many bioactivities, including antioxidative, anticancer, insecticidal, and bactericidal activities. Here, we designed a new scheme for synthesizing 2-arylfuranocoumarin derivatives by condensation, esterification, bromination, and Wittig reaction. We found that 2-thiophenylfuranocoumarin (Iy) had excellent photosensitive activity. Three Iy concentrations (LC25, LC50, and LC75) were used to treat the fourth instar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…However, natural furanocoumarin compounds have poor biological activity against pests, therefore, based on the structure of furanocoumarin, the authors designed and synthesized a series of 2-substituted furanocoumarin derivatives to increase the π-conjugated system in the furanocoumarin structure. In the early stage of our laboratory work, it was also confirmed that 2-thiophenefurocoumarin had excellent photosensitivity to the fourth instar larvae of Aedes aegypti and induced midgut tissue apoptosis [ 17 ]. In this study, 39 compounds were obtained ( Text S1, Figure S1 ).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, natural furanocoumarin compounds have poor biological activity against pests, therefore, based on the structure of furanocoumarin, the authors designed and synthesized a series of 2-substituted furanocoumarin derivatives to increase the π-conjugated system in the furanocoumarin structure. In the early stage of our laboratory work, it was also confirmed that 2-thiophenefurocoumarin had excellent photosensitivity to the fourth instar larvae of Aedes aegypti and induced midgut tissue apoptosis [ 17 ]. In this study, 39 compounds were obtained ( Text S1, Figure S1 ).…”
Section: Introductionmentioning
confidence: 74%
“…The synthesis of the compounds in the manuscript refers to the previous research of the College of Plant Protection, Hainan University [ 17 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Normally in insects, the SOD enzyme scavenges O 2– to H 2 O 2 , which is then converted to H 2 O by CAT and POD enzymes . As depicted in Figure and Tables S3–S5 (see the Supporting Information), the changes of CAT, POD, and SOD enzyme activities of S.…”
Section: Resultsmentioning
confidence: 97%
“…The development of insulin resistance affects oxidative stress in diabetic mice, leading to a significant increase in the levels of reactive oxygen species (ROS) and MDA in mice ( Li et al, 2021 ). Previous studies have proven that a large number of antioxidant enzymes in organisms, such as SOD, T-AOC and GSH-PX, can suppress oxidative stress by scavenging ROS levels ( Liu S. W. et al, 2020 ; Wu et al, 2021 ). The liver is the largest metabolic organ possessing abundant antioxidant enzymes.…”
Section: Resultsmentioning
confidence: 99%